SYSTEMATIC LITERATURE REVIEW: PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA KOMUNIKASI PUSTAKAWAN DAN PEMUSTAKA - laili, nazilatul; Zein, Labibah (Halu Oleo University Kendari, 2023)
ABSTRACTThis article aims to elaborate on the use of social media as an effective means of communication for librarians and librarians, using a Systematic Literature Review with a comparison of journal articles, to previous research which will be discussed in this article. The method used in this research is a literature review that is carried out by reading some collection materials, and several journals that are references and are related to the use of social media as a means of communication for librarians and users. The data analysis technique carried out relates to five journal articles that focus on librarian and user communication. The results and discussion of this article found that social media is a medium that provides information and communication for librarians and users. Until now it has become a benchmark to determine the level of progress of the library. Likewise with the advancement of information and communication technology which is so fast and has a tremendous influence on the development of libraries. The conclusions here broadly state that these five journal articles focus on the theme of communication between librarians and users through social media. The difference lies in the focus and research methods used in each journal.